Impact of pharmacist-led interventions on medication adherence and clinical outcomes in patients with hypertension and hyperlipidemia: A scoping review of published literature - Elnaem, Mohamed Hassan Abdelaziz; Rosely, Nur Fatin; Al-hifany, Abdullah; Elrggal, Mahmoud; Cheema, Ejaz (Dove Medical Press, 2020)
Background: The aim of this study was to provide a scoping review of the impact of pharmacist-led interventions on medication adherence and clinical outcomes in patients with hypertension and hyperlipidemia. Methods: A scoping review was conducted using pre-defined search terms in three scientific databases, including Google Scholar, ScienceDirect, and PubMed. A multi-stage screening process that considered relevancy, publication year (2009– 2019), English language, and article type (original research) was followed. Review articles, meta-analysis studies, and conference proceedings were excluded. Data charting was done in an iterative process using a study-specific extraction form. Results: Of the initially identified 681 studies, 17 studies with 136,026 patients were included in the review. Of these, 16 were randomized controlled trials, while the remaining study was a retrospective cohort study. The majority of pharmacist-led interventions were face-to-face counseling sessions (n=8), followed by remote- or telephone-based interventions (n=5) and multi-faceted interventions (n=4). The majority of the studies (n=7) used self-reported adherence measures and pharmacy refill records (n=8) to measure the rate of adherence to prescribed medications. Eleven of the included studies reported a statistically significant (P< 0.05) impact on medication adherence. Overall, twelve studies assessed the effect of the interventions on the clinical outcome measures; of these, only four studies were associated with significant impact. Conclusion: Pharmacist-led interventions were associated with improved patients’ adherence to their medications but were less likely to be consistently associated with the attainment of clinical outcomes. Face-to-face counseling was the most commonly used intervention; while, the multi-faceted interventions were more likely to be effective in improving the overall outcome measures. The rigorous design of targeted interventions with more frequent follow-ups, careful consideration of the involved medications, and patients’ characteristics could increase the effectiveness of these interventions.